2011
DOI: 10.1038/hdy.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus half-tetrad analysis and centromere mapping in citrus: evidence of SDR mechanism for 2n megagametophyte production and partial chiasma interference in mandarin cv ‘Fortune’

Abstract: The genetic structure of 2n gametes and, particularly, the parental heterozygosity restitution at each locus depends on the meiotic process by which they originated, with firstdivision restitution and second-division restitution (SDR) being the two major mechanisms. The origin of 2n gametes in citrus is still controversial, although sexual polyploidisation is widely used for triploid seedless cultivar development. In this study, we report the analysis of 2n gametes of mandarin cv 'Fortune' by genotyping 171 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
147
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(155 citation statements)
references
References 39 publications
5
147
0
3
Order By: Relevance
“…In the present study, the rate of maternal HR of all 25 markers varied from 0% to 100%, with a heterozygosity rate <50% for 10 markers, suggesting that SDR may be the mechanism underlying 2n megagametophyte formation. Cuenca et al [38] reported that maternal heterozygosity transmitted to each SDR 2n megagametophyte varied from 15.38% to 100%, with a mean value of 54.98%. In this study, based on all loci analyzed, the rate of maternal HR transmitted to each triploid hybrid ranged from 27.78% to 75.00%, with a mean of 51.46%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rate of maternal HR of all 25 markers varied from 0% to 100%, with a heterozygosity rate <50% for 10 markers, suggesting that SDR may be the mechanism underlying 2n megagametophyte formation. Cuenca et al [38] reported that maternal heterozygosity transmitted to each SDR 2n megagametophyte varied from 15.38% to 100%, with a mean value of 54.98%. In this study, based on all loci analyzed, the rate of maternal HR transmitted to each triploid hybrid ranged from 27.78% to 75.00%, with a mean of 51.46%.…”
Section: Discussionmentioning
confidence: 99%
“…Frost and Soost, (1968) and Kobayashi et al (1981) proposed that chromosome doubling in nucellar tissue might be the general mechanism underlying this process. It was confirmed by Aleza et al (2011). This characteristic could be under genetic control (Barrett and Hutchison, 1978) and/or affected by environmental conditions (Hutchison and Barrett, 1981;Aleza et al, 2011).…”
Section: Doubled-diploidsmentioning
confidence: 70%
“…This characteristic can be a problem when apomictic genotypes are used as female parents in sexual hybridization. In this context, molecular marker techniques allow the differentiation between zygotic and nucellar seedlings and they have been developed and introduced within citrus breeding programs (Luro et al, 1995;Ruiz et al, 2000;Aleza et al, 2011). Nevertheless at practical level it is very difficult to recover large population of hybrids using apomictic genotypes as female parents.…”
Section: Reproductive Biologymentioning
confidence: 99%
See 2 more Smart Citations